Akute unilaterale Sehstörung nach COVID-Impfung - Bachmann, P.; Mardin, Christian Y.; Bartsch, A. J.; Weller, Julia (Ophthalmologe, 2021)
CRIS-Team Scopus Importer:2021-10-01

Characterisation of ectasia after penetrating keratoplasty in keratoconus eyes using anterior segment optical coherence tomography - Weller, Julia; Hübner, Lisa; Kruse, Friedrich; Tourtas, Theofilos (British Journal of Ophthalmology, 2023)
Background/aims: Ectasia of the cornea can occur decades after penetrating keratoplasty (PK), especially in keratoconus eyes. The purpose of this study was to characterise ectasia after PK by morphological findings in anterior segment optical coherence tomography (AS-OCT). Methods: In this retrospective, single-centre case series, 50 eyes of 32 patients with a history of PK at an average of 25±10 years earlier were included. The eyes were classified either as ectatic (n=35) or as non-ectatic (n=15). The main parameters included central corneal thickness (CCT), lowest corneal thickness at the interface (LCTI), anterior chamber depth, graft-host interface angle at the thinnest point and host cornea-iris angle. Furthermore, steep and flat keratometry readings obtained by AS-OCT (CASIA-2, Tomey) and Scheimpflug tomography (Pentacam, Oculus) were assessed. OCT findings were correlated with clinical grading of ectasia. Results: There was a highly significant difference in LCTI, graft-host interface angle and anterior chamber depth (in pseudophakic eyes) between the groups. The ratio calculated by the quotient of LCTI divided by CCT was significantly lower in ectatic than non-ectatic eyes (p<0.001). In eyes with an LCTI/CCT ratio of ≤0.7, the OR for the occurrence of a clinical detectable ectasia was 2.4 (CI 1.5 to 3.7). Steep keratometry values were significantly higher in ectatic eyes. Conclusion: AS-OCT is a helpful tool to recognise and quantify ectasia in post-PK eyes objectively.
CRIS-Team Scopus Importer:2023-04-21
Keywords: Cornea; Imaging; Treatment Surgery

Descemet membrane endothelial keratoplasty: analysis of clinical outcomes of patients with 8-10 years follow-up - Weller, Julia; Kruse, Friedrich; Tourtas, Theofilos (International Ophthalmology, 2022)
Purpose This study aimed to evaluate the clinical outcomes up to 10 years after Descemet membrane endothelial keratoplasty (DMEK). Methods In this retrospective, consecutive, single-center case series the medical files of eyes which have received DMEK between 2009 and 2012 for the treatment of endothelial dysfunction was evaluated regarding follow-up time and clinical outcomes. Annual examinations of best-corrected visual acuity (BCVA), endothelial cell density (ECD), central corneal thickness (CCT) of 66 eyes which fulfilled the criterion of a minimum of 8 years follow-up were analyzed. Results BCVA improved from 0.55 +/- 0.37 logMAR (n = 54) to 0.15 +/- 0.11 (n = 47) in eyes without ocular comorbidities one year after DMEK (p < 0.001), and remained stable up to 10 years after DMEK. Mean ECD decreased to 744 +/- 207 cells/mm(2) (n = 39) after 9 years, and to 729 +/- 167 cells/mm(2) (n = 21) after 10 years, respectively. CCT decreased from 650 +/- 67 mu m before DMEK to 525 +/- 40 mu m (n = 56) after 1 year, increasing slowly to 563 +/- 40 mu m (n = 39) after 9 years, and to 570 +/- 42 mu m (n = 21) after 10 years, respectively. Graft failure occurred in 4 of 66 eyes after year 8. These 4 eyes required repeat DMEK after 101-127 months. Conclusion This study shows the long-term outcomes in a small subset of DMEK grafts. Visual acuity remained stable in spite of slowly increasing corneal thickness and diminishing endothelial cell density during the 10-year period after DMEK.
CRIS-Team WoS Importer:2022-01-14

Differences in Guttae Ultramorphology in Relation to Visual Function in Fuchs Endothelial Corneal Dystrophy - Weller, Julia; Bennemann, Maximilian; Tourtas, Theofilos; Kruse, Friedrich; Schlötzer-Schrehardt, Ursula (Cornea, 2024)
PURPOSE: The purpose of this study was to investigate the differences in guttae ultramorphology and their relation to visual function in eyes with Fuchs endothelial corneal dystrophy (FECD). METHODS: Thirty FECD eyes without ocular comorbidities were included. Visual functional parameters (best-corrected visual acuity with high-contrast and low-contrast letters and contrast sensitivity/LogCS) and corneal morphology measured with Scheimpflug tomography (Pentacam) were assessed. The surgically removed Descemet membranes were examined by light and transmission electron microscopy. RESULTS: Preoperative mean best-corrected visual acuity (logarithm of the minimum angle of resolution) was 0.52 ± 0.18, LogCS 0.96 ± 0.21 and central corneal thickness 640 ± 55 μm. All eyes had signs of subclinical corneal edema in Scheimpflug tomography; clinically visible corneal edema was present in 40% of eyes. Histological findings included a posterior fibrillar zone (PFZ) in 10 specimens (33%) and abnormal collagen depositions in Descemet membranes in 14 specimens (47%). Guttae buried within the PFZ were present only in eyes with clinically visible edema (n = 4, 13%). There was no difference in visual function results and tomography parameters between eyes with and without PFZ or between protruding guttae and guttae embedded in a PFZ, respectively. CONCLUSIONS: Guttae morphology and density were not correlated with visual functional parameters. Guttae buried in a PFZ occurred only in eyes with clinically manifest edema, and thereby, they are an ultramorphological sign for advanced FECD. Subclinical edema was present in all eyes and might be more relevant for quality of vision than guttae ultramorphology.
CRIS-Team Scopus Importer:2024-10-11

Dysregulated Retinoic Acid Signaling in the Pathogenesis of Pseudoexfoliation Syndrome - Zenkel, Matthias; Hoja, Ursula; Gießl, Andreas; Berner, Daniel; Hohberger, Bettina; Weller, Julia; König, Loretta; Huebner, Lisa; Ostermann, Thomas A.; Gusek-Schneider, Gabriele; Kruse, Friedrich; Pasutto, Francesca; et al. (International Journal of Molecular Sciences, 2022)
Pseudoexfoliation (PEX) syndrome, a stress-induced fibrotic matrix process, is the most common recognizable cause of open-angle glaucoma worldwide. The recent identification of PEX-associated gene variants uncovered the vitamin A metabolic pathway as a factor influencing the risk of disease. In this study, we analyzed the role of the retinoic acid (RA) signaling pathway in the PEX-associated matrix metabolism and evaluated its targeting as a potential candidate for an anti-fibrotic intervention. We provided evidence that decreased expression levels of RA pathway components and diminished RA signaling activity occur in an antagonistic crosstalk with TGF-beta 1/Smad signaling in ocular tissues and cells from PEX patients when compared with age-matched controls. Genetic and pharmacologic modes of RA pathway inhibition induced the expression and production of PEX-associated matrix components by disease-relevant cell culture models in vitro. Conversely, RA signaling pathway activation by natural and synthetic retinoids was able to suppress PEX-associated matrix production and formation of microfibrillar networks via antagonization of Smad-dependent TGF-beta 1 signaling. The findings indicate that deficient RA signaling in conjunction with hyperactivated TGF-beta 1 /Smad signaling is a driver of PEX-associated fibrosis, and that restoration of RA signaling may be a promising strategy for anti-fibrotic intervention in patients with PEX syndrome and glaucoma.
CRIS-Team WoS Importer:2022-06-24
Keywords: pseudoexfoliation syndrome; pseudoexfoliation glaucoma; retinol; retinoic acid; extracellular matrix; fibrosis; TGF-β1

Focus on Ophthalmopathology - Orbital Infections from Hordeolum to Necrotizing Fasciitis Schwerpunkt Ophthalmopathologie Orbitainfektion: vom Hordeolum bis zur nekrotisierenden Fasziitis - Weller, Julia; Messmer, Elisabeth (Klinische Monatsblätter für Augenheilkunde, 2022)
(Peri)orbital infections comprise a multitude of diagnoses, ranging from common hordeolum to rare but life-threatening necrotizing fasciitis. However, these disease entities are rarely diagnosed by an ophthalmic pathologist because (peri)orbital infections are usually diagnosed clinically, with the help of imaging and microbiological techniques when indicated. In this review article, the role of ophthalmopathology in the diagnosis of (peri)orbital infections is illustrated on the basis of several exemple diagnoses. An infectious hordeolum must be distinguished from a noninfectious chalazion. A nodular thickening of the eyelid, which is diagnosed and treated as a chalazion, can hide a malignant neoplasia. The correct diagnosis and treatment of canaliculitis is often delayed. In this context the most common causative organism, Actinomyces, can be depicted histologically, as can lacrimal stones/dacryoliths. Necrotizing fasciitis is a rapidly worsening infection of the fascia, which can lead to necrosis, sepsis, and death. During the Sars-CoV2 pandemic, an increased incidence of mucormycosis cases was observed, especially in India. This superinfection was facilitated by the widespread use of steroids and immunosuppression. Histologically, it is possible to visualize infiltration of vessel walls by the fungus. Ophthalmopathology contributes to the diagnosis and to understanding the pathophysiology of these diseases.
CRIS-Team Scopus Importer:2022-08-05
Keywords: infectious diseases; orbit; pathology

Keratomalacia and corneal perforation in vitamin A deficiency: Anterior-segment optical-coherence-tomography and histological findings - Weller, Julia; Tourtas, Theofilos; Kruse, Friedrich (American Journal of Ophthalmology Case Reports, 2024)
Purpose: To describe the histological findings and results of anterior-segment optical-coherence-tomography (AS-OCT) in patients with severe keratomalacia and corneal perforation due to vitamin-A deficiency (VAD). Observations: Four patients (3 female, 1 male) with moderate to severe VAD were included in this single-center case series. Keratomalacia/corneal perforation was diagnosed by slit-lamp examination. The findings were documented using photographs and AS-OCT imaging (CASIA-2, Tomey corporation, Nagoya, Japan). Ocular and general medical findings including causes of VAD are reported. VAD was severe (<20 ng/ml) in two patients with chronic alcoholism, and moderate (205/231 ng/ml) in two patients with cachexia. Corneal perforation occurred in 3 out of 4 patients. One patient had severe keratomalacia with impending perforation and massive conjunctival folds with Bitot's spots, which vanished soon after initiation of vitamin A supplementation. In three cases, corneal specimens obtained during anterior lamellar keratoplasty were assessed histologically by light-microcopy. The histological specimens showed massive epithelial thickening and a pronounced granular layer of the corneal epithelium. Conclusions and importance: Keratomalacia leading to corneal perforation is a rare, but possible complication also in countries with sufficient general food supply. The clinico-pathological correlation between AS-OCT and histological findings in patients with VAD is shown in this case series. Typical Bitot's spots were present only in one patient and can be visualized by AS-OCT.
CRIS-Team Scopus Importer:2024-09-20
Keywords: Corneal perforation; Optical coherence tomography; Vitamin A deficiency

Long-Term Outcomes of Keratoprosthesis With Biological Haptic: A Review of 25 Years of Single-Center Surgeries - Angerer, Maximilian; Weller, Julia; Kruse, Friedrich; Hille, Konrad (Cornea, 2024)
Purpose: To study the outcome of eyes that underwent surgery for keratoprosthesis with a biological haptic, osteo-odonto-keratoprosthesis (OOKP) or tibia keratoprosthesis, by a single surgeon over a time span of more than 25 years. Methods: One hundred thirty eyes that had received a keratoprosthesis with a biological haptic between 1994 and 2022 by a single surgeon were included in this retrospective analysis. Main outcome parameters were postoperative best corrected visual acuity, postoperative refractive error, postoperative complications, anatomical and functional survival of the prosthesis as well as comparison of subgroups of the 2 different types (OOKP n = 78; tibia keratoprosthesis n = 52) of keratoprostheses, and subgroup analysis of different indications for surgery. Patients were examined every 6 months. Results: The longest follow-up was 25.8 years. Reasons for implantation were graft-vs-host disease (6.9%), vascularized corneas and dry eye (22.9%), physical or chemical burns (29.8%), Stevens-Johnson syndrome (9.9%), and ocular cicatricial pemphigoid (30.5%). The functional success rate with postoperative visual acuity of better than 0.7 log MAR was achieved by 56.9%. The OOKP subgroup showed a better mean visual outcome. 14 keratoprostheses (10.7%) had to be explanted over the whole time span. In the time leading to explantation, refraction showed a statistically significant myopic shift when compared with the non-explanted prosthesis. Anatomical survival rates were better for the OOKP in the first 12 years after implantation. Conclusions: The study shows that keratoprosthesis with a biological haptic has favorable long-term outcomes. The retention rate stayed very high with excellent functional outcomes.
CRIS-Team Scopus Importer:2024-08-16
Keywords: keratoprosthesis; osteo-odonto-keratoprosthesis; tibia-keratoprosthesis

Management of Late Descemet's Membrane Detachment after Penetrating Keratoplasty in Keratoconus - Weller, Julia; Kruse, Friedrich; Schlötzer-Schrehardt, Ursula; Tourtas, Theofilos (Cornea, 2022)
Purpose:The purpose of this study was to describe the feasibility of Descemet membrane endothelial keratoplasty (DMEK) as a treatment modality for spontaneous detachment of DM (DMD) decades after penetrating keratoplasty (PK) for keratoconus.Methods:We describe the clinical characteristics and therapeutic surgical approach in 6 eyes of 5 patients with DMD. Clinical images, anterior segment optical coherence tomography scans, and histological findings are presented.Results:Mean age of patients at time of diagnosis was 60 years (range 56-66 years). Mean interval between PK and occurrence of DM detachment was 36 years (range 29-45 years). In 4 of 6 eyes, air injections into the anterior chamber were initially attempted to reattach DM to the stroma but without long-lasting effect. Two eyes underwent repeat PK because of pronounced ectasia after long-standing DMD and stromal scars. DMEK was performed successfully in 4 eyes leading to an increase in visual acuity and a reduction in central corneal thickness. Electron microscopy showed abnormal vacuolar inclusions and collagenous material in the posterior nonbanded layer and a separation of the anterior banded layer from the posterior nonbanded layer.Conclusions:This case series provides evidence that DMEK is a viable option in eyes with spontaneous DM detachment after PK. Visual outcome is limited by the persisting high astigmatism in the ectatic cornea. Illustrated by a small series of patients, the results of DMEK in this condition are presented and new findings about the pathophysiology are given.
CRIS-Team Scopus Importer:2022-11-25
Keywords: Descemet membrane detachment; DMEK; keratoconus

Refractive Outcomes After Descemet Membrane Endothelial Keratoplasty plus Cataract/Intraocular Lens Triple Procedure: A Fellow Eye Comparison - Augustin, Victor A.; Weller, Julia; Kruse, Friedrich; Tourtas, Theofilos (Cornea, 2021)
Purpose: Descemet membrane endothelial keratoplasty is often combined with phacoemulsification and intraocular lens implantation (DMEK + cataract/IOL triple procedure) in phakic patients. This procedure results in a refractive shift that is difficult to predict. The aim of this study was to evaluate the hypothesis that the refractive shift in the second eye follows the shift in the first eye. Methods: In this retrospective, single-center, consecutive case series, the refractive outcomes of 254 eyes of 127 patients who underwent DMEK + cataract/IOL triple procedure in both eyes for Fuchs endothelial corneal dystrophy have been analyzed. Main outcome measures were spherical equivalent outcome (shift calculations), best spectacle-corrected visual acuity, central corneal thickness, and posterior simulated keratometry. Results: The mean best spectacle-corrected visual acuity before surgery was 0.51 +/- 0.24 and increased to 0.19 +/- 0.15 (logMAR) after surgery (P < 0.001). After surgery, a mean hyperopic shift of 0.98 +/- 0.89 D was observed. The refractive shift was 1.03 +/- 0.93 D and 0.92 +/- 1.02 D, in the first and second eyes, respectively (P = 0.435). In a paired analysis, the mean difference of the refractive shift between the first and second eyes was 0.49 +/- 0.43 D. Conclusions: In our fellow eye comparison, the refractive shift after DMEK + cataract/IOL triple procedure in the second eye was comparable with the shift in the first eye. As a consequence, the refractive outcome of the first eye might serve as a reference for optimizing the refractive target in the second eye. Further studies investigating the influence of corneal parameters on refractive shift are needed for a more predictable lens power selection.
CRIS-Team WoS Importer:2021-11-26

Risk factors for ocular hypotony after XEN Gel Stent implantation - Galimi, Maria E.; Weller, Julia; Kruse, Friedrich; Lämmer, Robert (Graefes Archive For Clinical and Experimental Ophthalmology, 2022)
Purpose: To investigate the incidence of postoperative hypotony, and risk factors for the development of hypotony in eyes who had undergone XEN Gel Stent implantation. Methods: In this retrospective, single-centre case series, medical records of 170 consecutive eyes who had undergone XEN Gel Stent implantation with or without simultaneous phacoemulsification for primary or secondary open angle glaucoma were analysed. Primary outcome parameters were the incidence of postoperative hypotony and potential risk factors for its development, and secondary parameters were pre- and postoperative visual acuity, intraocular pressure (IOP), and number of IOP-lowering eye drops. Results: Postoperative hypotony ≤ 6 mmHg occurred in 57% of eyes. Hypotony was without complications in 70.1%, 13.4% had transient complications with spontaneous resolution, and 16.5% had complications requiring treatment. Mean visual acuity logMAR before surgery accounted for 0.47 ± 0.46 in all eyes and 0.47 ± 0.48 at the 4-week visit. There was no significant difference of BCVA in the group of eyes with and without postoperative hypotony before and after surgery. The mean IOP before surgery was 24.6 ± 8.4 mmHg and decreased significantly to 18.4 ± 10.2 after 4 weeks. Eyes with an axial length over 24.3 mm had a threefold increased risk for postoperative hypotony (OR 3.226, 95% confidence interval 1.121–9.279). This risk was decreased in eyes with simultaneous cataract surgery (OR 0.483, 95% confidence interval 0.258–0.903). Conclusion: In our sample, postoperative hypotony was a common complication after XEN Gel Stent implantation, but serious, persistent complications were rare. A longer axial length predisposes the eye for the development of hypotony.[Figure not available: see fulltext.].
CRIS-Team Scopus Importer:2022-10-21
Keywords: Glaucoma; Hypotony; Minimal invasive glaucoma surgery (MIGS); XEN Gel Stent

SD-OCT-histopathologic correlation in Schnabel’s cavernous optic nerve atrophy - Weber, C.; Mercieca, K.; Weller, Julia; Bulirsch, L. M.; Ach, T.; Holz, F. G.; Loeffler, K. U.; Herwig-Carl, M. C. (Eye, 2025)
Background: Until now, Schnabel’s cavernous optic nerve atrophy (SCONA) has solely been a histopathological diagnosis exhibiting variable degrees of optic nerve (ON) atrophy with characteristic cavernous spaces filled with acid mucopolysaccharides. We report the first correlation of histopathologic findings with spectral domain-optical coherence tomography (SD-OCT) imaging in SCONA. Methods: We examined the eye of an index patient with histopathologically identified SCONA who had undergone multimodal imaging before enucleation for iris ring melanoma. The extent of SCONA in the index patient and three other enucleated eyes with SCONA were determined histopathologically. The histopathological findings of our index patient were correlated with in vivo SD-OCT images before enucleation and compared to representative images from eyes with a normal versus glaucomatous optic disc. Results: Histopathologic examination of our index patient showed a pre- and intralaminar extension of SCONA. Atrophy of the inner retinal layers was observed corresponding to the extent of SCONA. Correlation with SD-OCT showed small intralaminar hyporeflective pseudocysts which were detected in multiple scans corresponding to the histologically affected areas. These changes were neither visible in scans of patients with glaucomatous atrophy nor those with a normal ON. Conclusions: We present the first correlation of clinical and pathological findings in SCONA and were able to identify distinct SD-OCT characteristics for this condition. These findings may help to detect SCONA in vivo and to study this rare entity clinically with regard to its clinical course, risk factors, and pathogenesis. However, more cases of SCONA are needed to confirm our findings.
CRIS-Team Scopus Importer:2025-02-17

Surprising histologic findings in a chronic corneal ulcer Überraschung in der Histologie bei einem chronischen Hornhautulkus - Steinhorst, K. A.; Weller, Julia (Die Ophthalmologie, 2023)
CRIS-Team Scopus Importer:2023-10-20

Type II Diabetes Mellitus Causes Extracellular Matrix Alterations in the Posterior Cornea That Increase Graft Thickness and Rigidity - Kingsbury, Kenten D.; Skeie, Jessica M.; Cosert, Krista; Schmidt, Gregory A.; Aldrich, Benjamin T.; Sales, Christopher S.; Weller, Julia; Kruse, Friedrich; Thomasy, Sara M.; Schlötzer-Schrehardt, Ursula; Greiner, Mark A. (Investigative Ophthalmology & Visual Science, 2023)
PURPOSE. There is a pressing need to investigate the impact of type II diabetes mellitus on the posterior cornea in donor tissues given its increasing prevalence and potential impact on endothelial keratoplasty surgical outcomes. METHODS. Immortalized human cultured corneal endothelial cells (CECs; HCEC-B4G12) were grown in hyperglycemic media for 2 weeks. Extracellular matrix (ECM) adhesive glycoprotein expression and advanced glycation end products (AGEs) in cultured cells and corneoscleral donor tissues, as well as the elastic modulus for the Descemet membrane (DMs) and CECs of diabetic and nondiabetic donor corneas, were measured. RESULTS. In CEC cultures, increasing hyperglycemia resulted in increased transforming growth factor beta-induced (TGFBI) protein expression and colocalization with AGEs in the ECM. In donor corneas, the thicknesses of the DM and the interfacial matrix (IFM) between the DM and stroma both increased from 8.42 ± 1.35 μm and 0.504 ± 0.13 μm in normal corneas, respectively, to 11.13 ± 2.91 μm (DM) and 0.681 ± 0.24 μm (IFM) in non-advanced diabetes (P = 0.013 and P = 0.075, respectively) and 11.31 ± 1.76 μm (DM) and 0.744 ± 0.18 μm (IFM) in advanced diabetes (AD; P = 0.0002 and P = 0.003, respectively). Immunofluorescence in AD tissues versus controls showed increased AGEs (P < 0.001) and markedly increased labeling intensity for adhesive glycoproteins, including TGFBI, that colocalized with AGEs. The elastic modulus significantly increased between AD and control tissues for the DMs (P < 0.0001) and CECs (P < 0.0001). CONCLUSIONS. Diabetes and hyperglycemia alter human CEC ECM structure and composition, likely contributing to previously documented complications of endothelial keratoplasty using diabetic donor tissue, including tearing during graft preparation and reduced graft survival. AGE accumulation in the DM and IFM may be a useful biomarker for determining diabetic impact on posterior corneal tissue.
CRIS-Team Scopus Importer:2023-08-11
Keywords: corneal biomechanics; corneal endothelial cells; corneal transplantation

Ultrastructural analysis of explanted CyPass microstents and correlation with clinical findings - Hübner, Lisa; Schlötzer-Schrehardt, Ursula; Weller, Julia; Hohberger, Bettina; Mardin, Christian; Lämmer, Robert (Graefes Archive For Clinical and Experimental Ophthalmology, 2022)
Purpose: The purpose of this study was to obtain insight into cellular processes after CyPass microstent implantation into the supraciliary space. With this knowledge, we expected to find some reason for surgical failure. Methods: Nine CyPass microstents of 8 patients with primary open-angle glaucoma (n = 1), pseudoexfoliation glaucoma (n = 5), uveitic glaucoma (n = 1), and posttraumatic open-angle glaucoma (n = 1) were explanted due to recurrence of IOP elevation, corneal decompensation, or persistent hypotony. The explants were processed for light and transmission electron microscopy. Results: Fibrotic material, consisting of collagen fibrils, microfibrils, pseudoexfoliation fibrils produced by activated fibroblasts, was detected in the stent lumen of 4/5 pseudoexfoliation glaucoma patients and also in posttraumatic open-angle glaucoma. Fibrotic material was also present on the outer surface and within fenestrations of the majority of stents. Complete absence of fibrotic reaction was noticed in 3 of 9 microstents. Conclusion: Although MIGS is known to be less invasive than conventional surgery, implants placed in the suprachoroidal space may be adversely affected by a fibrotic tissue reaction resulting in implant failure. Understanding mechanisms and risk factors leading to fibrotic scarring following antiglaucomatous surgery may help to develop novel strategies that improve surgical outcome.
CRIS-Team Scopus Importer:2022-03-18
Keywords: CyPass microstent; Fibrosis; Glaucoma; MIGS; Surgery failure